2015
DOI: 10.1108/afr-02-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting farmers’ willingness to purchase weather index insurance in the Hainan Province of China

Abstract: Purpose -The purpose of this paper is to explain the factors affecting farmers' willingness to purchase weather index insurance for crops in China, in the Province of Hainan, and to also provide additional background information on weather index insurance. Design/methodology/approach -A survey of 134 farmers was undertaken in Hainan, China, regarding their willingness to purchase weather index insurance. A probit regression model was used, and a number of variables were included to explain willingness of farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This can include the situation in which a farmer experiences a loss but does not receive a payment, or alternatively where a farmer does not experience an actual loss but still receives a payment. Therefore, reducing basis risk is likely to be necessary in order to successfully implement index-based weather insurance (Carter et al 2014;Clarke 2011;Elabed et al 2013;Jensen et al 2018;Lin et al 2015;Skees 2008).…”
Section: Indexed-based Weather Insurancementioning
confidence: 99%
“…This can include the situation in which a farmer experiences a loss but does not receive a payment, or alternatively where a farmer does not experience an actual loss but still receives a payment. Therefore, reducing basis risk is likely to be necessary in order to successfully implement index-based weather insurance (Carter et al 2014;Clarke 2011;Elabed et al 2013;Jensen et al 2018;Lin et al 2015;Skees 2008).…”
Section: Indexed-based Weather Insurancementioning
confidence: 99%
“…However, spatial basis risk may be reduced by using spatial interpolation techniques to create better estimates of weather conditions in the farmer's fields. Basis risk continues to be an important and challenging area of research, often limited by the amount of reliable data that is available (AAFC, 2012a;Lin et al, 2015). Major (1999) was one of the first academic papers to propose a method for analyzing basis risk as it applies to catastrophe derivative contracts.…”
Section: Basis Risk Reviewmentioning
confidence: 99%
“…Weather index insurance has become a popular subject in agricultural risk management with many papers devoted to its discussion (Heimfarth and Musshoff, 2011;Lin et al, 2015;Okhrin et al, 2013). Under these policies farmers receive payments if they experience adverse weather for their crops during the growing season.…”
Section: Chapter 6: Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu (2011) studied the achievements and challenges of China's weather index insurance programs and found that farmers had weak demand for such insurance. Lin et al (2015) found some factors affecting farmers' willingness to purchase weather index insurance in China and concluded that besides the recognition of risk itself, factors such as their type of agricultural products and farmers' trust to the insurer affect the farmers' willingness.…”
Section: Literature Reviewmentioning
confidence: 99%